Relationships between kinematic characteristics and ratio of forces during initial sprint acceleration - King, D.; Burnie, L.; Nagahara, R.; Bezodis, N. E. (Journal of Sports Sciences, 2022)
In track sprinting, acceleration performance is largely determined by the ability to generate a high ratio of forces (RF), but the technical features associated with this remain unknown. This study therefore investigated the relationships between selected kinematic characteristics and RF during the initial acceleration phase. Fourteen male sprinters completed two maximal 60 m sprints from a block start. Full-body kinematic and external kinetic data were obtained from the first four steps, and the relationships between selected kinematic characteristics and mean RF over the first four steps were determined. Placing the stance foot further behind (or less far in front of) the whole-body centre of mass at touchdown was significantly related to greater RF (r = -0.672), and more anterior orientation of the proximal end of the foot (r = -0.724) and shank (r = -0.764) segments at touchdown were also significantly related to greater RF. Following touchdown, greater ankle dorsiflexion range of motion during early stance was significantly related to greater RF (r = 0.728). When aiming to enhance RF during initial acceleration, practitioners should be encouraged to focus on lower leg configurations when manipulating touchdown distance, and the role of dorsiflexion during early stance is also an important consideration.